Development and Score-Validation of the Research Anxiety Rating Scale - Onwuegbuzie, Anthony John (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Most graduate students enrolled in programs within colleges of education are required to complete one or more research methodology courses as a necessary part of their degrees. Unfortunately, it appears that these courses are exceedingly difficult for many students, who typically experience underachievement. Many students experience high levels of anxiety in these classes. Onwuegbuzie (1997) theorized that the anxiety experienced in research methodology classes, termed research anxiety, represents a multidimensional phenomenon. Based on this conceptualization, the Research Anxiety Rating Scale (RARS) was developed. Thus, the purpose of this study was to describe the development of the RARS, as well as to delineate the psychometric properties of this scale. The RARS was administered to a sample of 262 graduate students (Study 2). Evidence of construct-related validity of the RARS was provided via an exploratory factor analysis, using a varimax rotation, in which seven specific factors were identified, explaining 57.1% of the variance in RARS scores. These seven factors were (a) fear of libraries, (b) fear of writing, (c) fear of statistics, (d) fear of conducting research, (e) fear of research language, (f) fear of research courses, and (g) perceived utility and competence. Evidence of criterion-related validity (i.e., concurrent validity) was established via statistically significant correlations between scores on the RARS and scores on the Statistical Anxiety Rating Scale (STARS), the Library anxiety Scale (LAS), and the Writing Apprehension Test (WAT). No gender differences were found with respect to the RARS total scale or subscales. The implications are discussed.